2015
DOI: 10.1158/2159-8290.cd-14-1057
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Analysis of Genetic Variants within Putative miRNA Binding Sites in Prostate Cancer

Abstract: Prostate cancer is the second most common malignancy among men worldwide. Genome-wide association studies (GWAS) have identified 100 risk variants for prostate cancer, which can explain ~33% of the familial risk of the disease. We hypothesized that a comprehensive analysis of genetic variations found within the 3′ UTR of genes predicted to affect miRNA binding (miRSNPs) can identify additional prostate cancer risk variants. We investigated the association between 2,169 miRSNPs and prostate cancer risk in a lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…For patients with early-stage cervical squamous cell carcinoma, miR-3162-5p was a member of a six-miRNA panel that was able to predict lymph node metastasis with an AUC of 0.9320 [39]. In prostate cancer, a probable role of miR-3162-5p in the mechanism underlining the increased prostate cancer risk with the kallikrein-related peptidase 3 (KLK3) rs1058205 miRSNP T-allele has been demonstrated [40]. Furthermore, in a recent study, the increased expression of miR-3162-5p in prostate tumor tissues has been associated with a higher Gleason grade; thus, indicating the possible use of miR-3162-5p in stratifying patients who are at risk of developing aggressive prostate cancer [41].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with early-stage cervical squamous cell carcinoma, miR-3162-5p was a member of a six-miRNA panel that was able to predict lymph node metastasis with an AUC of 0.9320 [39]. In prostate cancer, a probable role of miR-3162-5p in the mechanism underlining the increased prostate cancer risk with the kallikrein-related peptidase 3 (KLK3) rs1058205 miRSNP T-allele has been demonstrated [40]. Furthermore, in a recent study, the increased expression of miR-3162-5p in prostate tumor tissues has been associated with a higher Gleason grade; thus, indicating the possible use of miR-3162-5p in stratifying patients who are at risk of developing aggressive prostate cancer [41].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants in miRNA regulome may affect miRNA transcription and regulation of targeted genes, and finally contribute to the development of complex traits and diseases. Some GWAS‐based studies have comprehensively investigated the associations of single nucleotide polymorphisms (SNPs) in miRNA regulome with human traits and diseases . Bulik‐Sullivan et al .…”
mentioning
confidence: 99%
“…Some GWAS-based studies have comprehensively investigated the associations of single nucleotide polymorphisms (SNPs) in miRNA regulome with human traits and diseases. [17][18][19][20][21] Bulik-Sullivan et al systematically cataloged trait/disease-associated SNPs in miRNA promoter regions and identified a variant in the promoter of the miRNA let-7 linked with human height variation. 17 Williamson et al revealed that SNPs associated with miRNA expression were enriched in the significant GWAS signals of some special diseases.…”
mentioning
confidence: 99%
“…The 'winner's curse', the observation that effect sizes are often larger in the populations in which they are discovered, may be one reason why some SNPs failed to replicate, and why ORs were generally smaller in our cohort than previously found [27]. Previous studies have shown the utility of including functional evaluation, in an attempt to identify candidate risk loci below currently accepted statistical levels of genome-wide significance [28]. Functional characterization of the variants described here remains to be done.…”
Section: Discussionmentioning
confidence: 80%